REPRESENTASI PEMBANTU RUMAH TANGGA KULIT HITAM DALAM FILM THE HELP - Nani Kurniasari (Universitas Bunda Mulia, 2015)
Movie is an integral part of communication science. Its popular character makes the movie into the mass media are quite effective in distributing the values and ideology promoted by the manufacturer to a wide audience. The tendency of Hollywood movies of the last decade brought an emancipatory ideology. It can be seen from the movies that raised the issue of the release of the civil rights of black people, life stories that are full of discrimination among blacks with whites bloom visualized in the movie. In these movies seen how a small group of white people have contributed to the critical success of freedom struggle of the civil rights of blacks. As depicted in The Help movie which tells how African-American maids in the city of Jackson-Mississippi are discriminated againts by their boss, also about how they are empowered by a young white woman to write a book about the treatment of white families for which they work. The concept of political representation are reviewed based on socio-cultural background and find out who is behind all the cultural production. Approached qualitatively, the study from the perspective of the critical paradigm using critical discourse analysis by Norman Fairclough. The data collected in this study are primary data incorporated into the text of the main elements forming the chart contains a narrative based sequence, scene, and shot from the beginning to the end of the story using multilevel analysis between text, context, discursive practices, and socio-cultural. Keywords: critical discourse analysis, discrimination, emancipatory, movie, representation.